2017
DOI: 10.1155/2017/1502854
|View full text |Cite
|
Sign up to set email alerts
|

Aggression from Patients or Next of Kin and Exposure to Bullying Behaviors: A Conglomerate Experience?

Abstract: Although workplace violence and aggression have been identified as important stressors in the nursing profession, studies simultaneously comparing patient-initiated aggression and exposure to bullying behaviors at work are rather scarce. The aim of this study was to compare aggression from patients or next of kin and exposure to bullying behaviors in terms of prevalence, health-related quality of life outcomes, and potential overlap in those targeted. In the period of 2008-2009, data were collected among 2059 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 63 publications
(89 reference statements)
3
35
1
6
Order By: Relevance
“…Antão HS, et al Workplace violence in healthcare, Acta Med Port 2020 Jan;33(1): [31][32][33][34][35][36][37] cognitive activation that can be described as worrying or having repetitive thoughts, triggering autonomic arousal and emotional stress. 4 Length of exposure has been referred as determinant to the severity of these effects. 4,5 The impact of workplace violence on health is of greater concern when workers are permanently involved with other citizens which is the case of healthcare, 3 where the risk of aggression is four times higher than in the general private sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antão HS, et al Workplace violence in healthcare, Acta Med Port 2020 Jan;33(1): [31][32][33][34][35][36][37] cognitive activation that can be described as worrying or having repetitive thoughts, triggering autonomic arousal and emotional stress. 4 Length of exposure has been referred as determinant to the severity of these effects. 4,5 The impact of workplace violence on health is of greater concern when workers are permanently involved with other citizens which is the case of healthcare, 3 where the risk of aggression is four times higher than in the general private sector.…”
Section: Introductionmentioning
confidence: 99%
“…4 Length of exposure has been referred as determinant to the severity of these effects. 4,5 The impact of workplace violence on health is of greater concern when workers are permanently involved with other citizens which is the case of healthcare, 3 where the risk of aggression is four times higher than in the general private sector. 6 Additionally, it threatens the quality of the care provided to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, these indicators had low factor loadings (Einarsen et al, 2009), even beneath a threshold of .3 (Giorgi, Arenas, & Leon-Perez, 2011). Also, studies employing Latent Class (LC) Analysis to deal with the highly skewed distributions of negative acts have found that, on the one hand, targets of workplace bullying hardly reported acts of physical aggression, while on the other hand, targets of physical aggression rarely reported bullying behaviours (Einarsen et al, 2009;Leon-Perez et al, 2014;Reknes et al, 2017).…”
mentioning
confidence: 99%
“…I 2017 ble det publisert fire nye vitenskapelige artikler fra SUSSH i internasjonale tidsskrifter (35)(36)(37)(38). Tematikken i disse omfatter livsstilsfaktorer, arbeidsnarkomani, sykefravaer og mobbing, alle i sammenheng med arbeidstid.…”
Section: Forlenge Konsesjonstiden Publikasjoner Fra Undersøkelsenunclassified
“…Konklusjonen fra denne studien er at selv om mobbing på arbeidsplassen inntreffer relativt sjelden, vil det ha en betydelig negativ innvirkning på sykepleiernes helse, en innvirkning som er sterkere enn det å bli utsatt for aggresjon fra pasienter og pårørende. Helseledere bør ha som mål å skape og sikre et positivt arbeidsmiljø med nulltoleranse for mobbing (37).…”
Section: «Mobbing På Arbeidsplassen Vil Ha En Betydelig Negativ Innviunclassified